Structure-guided virtual screening reveals phytoconstituents as potent cathepsin B inhibitors: Implications for cancer, traumatic brain injury, and Alzheimer’s disease - Hassan, Nageeb; Furkan, Mohammad; Khan, Mohd Shahnawaz; Zuberi, Azna; Shahwan, Moyad; Shamsi, Anas (Frontiers in Molecular Biosciences, 2025)
Cathepsin B (CathB) is a lysosomal cysteine protease involved in various pathological and physiological processes and is becoming an attractive target for drug intervention in complex diseases like cancer, traumatic brain injury (TBI) and Alzheimer’s disease (AD). The aberrant expression of CathB drives tumor invasiveness and metastasis and exacerbates neurodegeneration and behavioral deficits in AD and TBI. However, current CathB inhibitors lack clinical translation due to poor selectivity, bioavailability, or toxicity, necessitating novel therapeutic candidates. To address this gap, an in silico screening was conducted through the structure-guided virtual screening with the IMPPAT 2 phytochemical library for potential CathB inhibitors. Using the control inhibitor CA-074Me as a benchmark, two phytoconstituents, Nicandrenone and Picrasidine M, emerged with superior binding affinities, ligand efficiency, and robust interactions with the active site residues of CathB. These molecules were further validated through molecular dynamics (MD) simulations, which supported their ability to bind stably to the CathB active pocket and thus likely hold their durable inhibitory activity. Remarkably, these phytoconstituents exhibited favorable pharmacokinetic and ADMET profiles, which validate their potential as lead compounds. The current study showed that these bioactive compounds could be developed as new CathB inhibitors, opening a new frontier for their use in the management of such diseases as cancer, TBI, and AD.